Effect of hand paddles and parachute on the index of coordination of competitive crawl-strokers - Telles, T.; Barbosa, A. C.; Campos, M. H.; Júnior, O. A. (Journal of Sports Sciences, 2011)
We investigated the effects of hand paddles and parachute on the relative duration of stroke phases and index of coordination of competitive crawl-strokers. Eleven male-swimmers (age: 21.9 ± 4.5 years; 50-m best time: 24.23 ± 0.75 s) were evaluated in four maximal-intensity conditions: without equipment, with hand paddles, with parachute, and with both hand paddles and parachute. Relative stroke phase duration of each arm, swimming velocity, and stroke rate were analysed from video (60 Hz). The index of coordination was quantified based on the lag time between propulsive phases of each arm, which defined the coordination mode as catch-up, opposition or superposition. The stroke rate decreased in all conditions (P < 0.05) and swimming velocity decreased with parachute and with paddles + parachutes (P < 0.05). The coordination mode changed from catch-up in free swimming (-2.3 ± 5.0%) to opposition with paddles (-0.2 ± 3.8%), parachute (0.1 ± 3.1%), and paddles + parachute (0.0 ± 3.2%). Despite these variations, no significant differences were observed in relative duration of right and left arm-stroke phases, or in index of coordination. We conclude that the external resistances analysed do not significantly influence stroke phase organization, but, as a chronic effect, may lead to greater propulsive continuity.